PENGARUH MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI ANIMAKER TERHADAP HASIL BELAJAR IPAS SISWA KELAS V DI SD NEGERI 41 KARANG TANGAH - Afrida, Nur; Dwiana, Ari Aprillia (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
This study aims to determine the "influence of animaker technology-based learning media on the science learning outcomes of fifth-grade students at SD Negeri 41 Karang Tangah" in the 2025/2026 academic year. In this study, there were low student learning outcomes, especially in science learning, in the initial observations carried out, it was seen that teacher activities during teaching and learning activities did not pay attention to the use of technology-based learning media which caused some students to be less enthusiastic in participating in learning activities. Science learning that took place was still with a conventional learning system thick with a learning atmosphere that was considered less appropriate to the dynamics of the increasingly rapid development of science and technology. This population consisted of 14 students, this type of research used a quantitative approach with an experimental method with a Quasi-experimental type. Data were collected through pretest and posttest sheets. Based on the analysis of student data, the average value obtained with the pretest was 44, while the average posttest value was 74. This was shown through the results of the hypothesis test analysis carried out with the t-test with the criteria of t count > t table, namely (5.558 > 1.688). Thus, researchers suggest that teachers can use learning media in the teaching and learning process.